Metformin Shortens Prolonged QT Interval in Diabetic Mice by Inhibiting L-Type Calcium Current: A Possible Therapeutic Approach - Wang, Hui; Wang, Cao; Lu, Yuan; Yan, Yan; Leng, Dongjing; Tian, Shanshan; Zheng, Dongjie; Wang, Zhiguo; Bai, Yunlong (Frontiers in Pharmacology, 2020)
The incidence and mortality of cardiovascular disease in diabetic patients are 2-3 times higher than those in non-diabetic patients. Abnormal function of L-type calcium channel in myocardial tissue might result in multiple cardiac disorders such as a prolonged QT interval. Therefore, QT prolongation is an independent risk factor of cardiovascular disease in patients with diabetes mellitus. Metformin, a hypoglycemic agent, is widely known to effectively reduce the occurrence of macrovascular diseases. The aim of the present study was to evaluate the effect of metformin on prolonged QT interval and explore potential ionic mechanisms induced by diabetes. Diabetic mouse models were established with streptozotocin and an electrocardiogram was used to monitor the QT interval after 4 weeks of metformin treatment in each group. Action potential duration (APD) and L-type calcium current (ICa-L) were detected by patch-clamp in isolated mice ventricular cardiomyocytes and neonatal cardiomyocytes of mice. The expression levels of CACNA1C mRNA and Cav1.2 were measured by real-time PCR, western blot and immunofluorescence. A shortened QT interval was observed after 4 weeks of metformin treatment in diabetic mice. Patch-clamp results revealed that both APD and ICa-L were shortened in mouse cardiomyocytes. Furthermore, the expression levels of CACNA1C mRNA and Cav1.2 were decreased in the metformin group. The same results were also obtained in cultured neonatal mice cardiomyocytes. Overall, these results verify that metformin could shorten a prolonged QT interval by inhibiting the calcium current, suggesting that metformin may play a role in the electrophysiology underlying diabetic cardiopathy.